Melatonin epigenetic potential on testicular functions and fertility profile in varicocele rat model is mediated by silent information regulator 1. (21st February 2022) - Abo El Gheit, Rehab E.; Soliman, Nema A.; Nagla, Salah A.; El‐Sayed, Rehab M.; Badawi, Ghada A.; Emam, Marwa N.; Abdel Ghafar, Muhammad Tarek; Ibrahim, Marwa A. A.; Elswaidy, Noha R. M.; Radwan, Doaa A.; Alshenawy, Hanan A.; Khaled, Howayda E.; et al.
Abstract : Background and Purpose: Varicocele is a leading cause of male infertility. Melatonin is a highly pleiotropic neurohormone. We aimed to characterize the melatonin epigenetic potential in varicocele and the involved molecular mechanisms. Experimental Approach: Fifty‐two male albino rats were randomly divided into four groups (13 rats each): control (I), melatonin (II), varicocele (III) and melatonin treated varicocele (IV) groups. Left varicocele was induced by partial left renal vein ligation. Reproductive hormones, epididymal sperm functional parameters, testicular 3/17 β‐hydroxysteroid dehydrogenases, antioxidant enzymes, malondialdehyde, nicotinamide adenine dinucleotide phosphate oxidase, 8‐hydroxy‐2′‐deoxyguanosine and histopathological/Johnsen's score were evaluated. Flow cytometry and Comet were carried out to explore extent of sperm and testicular DNA damage. Testicular expression of silent information regulator 1 (SIRT1), forkhead transcription factors‐class O (type1) (FOXO1), tumour suppressor gene, P53, cation channels of sperm (CatSper) and steroidogenic acute regulatory protein was evaluated by western blot technique. Testicular expression of Bcl‐2 and its associated X protein and nuclear factor kappa‐light‐chain‐enhancer of activated B cells were assayed by immunohistochemical staining. Testicular miR‐34a expression was quantified by quantitative reverse transcription‐polymerase chain reaction. Key Results: The varicocele induced testicular histological injury, enhanced oxidative stress, P53‐mediated apoptosis, DNA damage and increased testicular miR‐34a expression paralleled with down‐regulated SIRT1/FOXO axis. Melatonin treatment of varicocele rats displayed antioxidant/anti‐apoptotic efficacy and improved reproductive hormones axis, CatSper expression and fertility parameters. MiR‐34a/SIRT1/FOXO1 epigenetic axis integrates testicular melatonin mediated intracellular transduction cascades in varicocele. Conclusion and Implications: Melatonin can be used as an adjuvant therapy to improve varicocele and its complication. Abstract :